Development and Validation of the Spectrophotometric Method for the Quantitative Determination of Azlocillin in Pure Substance and Medical Preparation - Karpova, Svitlana P. (Asian Journal of Pharmaceutics (AJP), 2019)
Objective: The kinetic of conjugated reactions of S-oxidation and perhydrolysis of Azlocillin (Azl) with potassium caroate in alkaline medium is studied by the increase of forming product light absorbance at 275 nm. Materials and Methods: SecuropenÂ® - powder Azl sodium in flacons for the preparation of solution for injections (Azl 1.0 g and 5.0 g) was used for analysis. Peroxymonosulfate acid as triple potassium salt 2ÐšÐSO5âˆ™ÐšÐSO4âˆ™K2SO4 (OxoneÂ®) of â€œextra pureâ€ qualification was used as oxidant. A scheme of peroxyacid oxidation and perhydrolysis conjugated reactions of Azl by means of potassium caroate is proposed. A new spectrophotometric method for the quantitative determination of sodium Azl in SecuropenÂ® preparation using potassium caroate (KHSO5) as an analytical reagent was proposed. Results: At pH 2â€“3 for 1 mole of penicillin, 1 mole of KHSO5 is consumed, and the quantitative interaction is achieved within a time of more than 1 min (observation time). The results were obtained by the recommended procedure for seven replicate titrations of mixtures containing the three species at various concentrations. Relative standard deviation (RSD) = (0.96â€“2.02) %, Î´ = (+0.49 â€¦ â€“ 0.33)%. It can be seen that Azl can be determined successively with good accuracy and reproducibility. Conclusions: The new procedure was developed and the ability of quantitative determination of penicillin in pharmaceutical preparation SecuropenÂ® by spectrophotometric method using potassium caroate (KHSO5) as analytical reagent was shown.